2015
DOI: 10.1016/j.gca.2015.06.013
|View full text |Cite|
|
Sign up to set email alerts
|

Isotopic and geochemical characterization of fossil brines of the Cambrian Mt. Simon Sandstone and Ironton–Galesville Formation from the Illinois Basin, USA

Abstract: Geochemical and isotopic characteristics of deep-seated saline groundwater provide valuable insight into the origin and evolving composition, water-rock interaction, and mixing potential of fossil brines. Such information may yield insight into intra-and interbasinal brine movement and relationships between brine evolution and regional groundwater flow systems. This investigation reports on the d 18 O and dD composition and activity values, 87 Sr/ 86 Sr ratios and Sr concentrations, and major ion concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…To conclude, when the whole Paris Basin hydrogeological scenario is considered, it shares numerous similarities with the fluid flow histories recorded in other intracratonic basins with comparable architecture, such as the Illinois Basin (Stueber & Walter, ; Labotka et al ., ) or the Michigan Basin (Wilson & Long, ). Indeed, these basins also experienced late stage infiltration of meteoric fluids into more ancient saline evaporative waters.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, when the whole Paris Basin hydrogeological scenario is considered, it shares numerous similarities with the fluid flow histories recorded in other intracratonic basins with comparable architecture, such as the Illinois Basin (Stueber & Walter, ; Labotka et al ., ) or the Michigan Basin (Wilson & Long, ). Indeed, these basins also experienced late stage infiltration of meteoric fluids into more ancient saline evaporative waters.…”
Section: Discussionmentioning
confidence: 99%
“…The very low Cl/Br mass ratio of this groundwater (149 to 216; Panno, ISGS, unpublished data) suggests that the salinity originates from a mixture of brines from the underlying Cambrian and Ordovician strata, and perhaps crystalline basement brines (Table S1, Supporting Information). The upwelling of crystalline basement brines at least into lower Cambrian strata is likely, based on work by Panno et al () and Labotka et al (, ).…”
Section: Resultsmentioning
confidence: 98%
“…The salinity of the groundwater within the basin is typically stratified (Panno and Hackley ) with most shallow groundwater containing Na and Cl − concentrations in sand and gravel aquifers between 1 and 15 mg/L for each ion (Panno et al ). The sources of the Na‐Ca‐Cl‐type brines of the Illinois Basin were studied by Stueber et al (), Walter et al (), Stueber and Walter (, ), Panno et al (), and Labotka et al (, ). These studies suggested, based on halide–halide and halide–cation ratios, and stable isotopes ( 87 Sr/ 86 Sr, δ D and δ 18 O), that brines of the Illinois Basin originated as evaporated seawater and are composed of four geochemically distinct fluid regimes (Cambrian, Ordovician, Silurian–Devonian, and Mississippian–Pennsylvanian).…”
Section: Geology and Hydrogeology Of The Illinois Basinmentioning
confidence: 99%
“…Porewaters were sampled through a single, multi-level observation well at two and six discrete depths in the Upper and Lower units, respectively (the low permeability of the Middle unit precluded sampling). While the Upper unit has been shown to have experienced minor dilution (Panno et al, 2013;Labotka et al, 2015), both Upper and Lower porewaters were recently interpreted as dominated by modified Cambrian seawater (Labotka et al, 2016), illustrating the long-standing isolation of these brines.…”
Section: Lettermentioning
confidence: 99%
“…Table 1 Porewaters sampled at nine discrete depths within the MSS from a single, multi-level observation well. All data except the δ 37 Cl and δ 81 Br were measured at the ISGS (Panno et al, 2013;Labotka et al, 2015 In the Lower unit, δ 37 Cl and δ 81 Br are respectively enriched by +0.67 ‰ and +1.15 ‰. Given the thickness of the sediment column (~180 m), these variations are typically within the equilibrium range for temperatures between 50 °C (current temperature of the aquifer) and 130 °C (maximal cementation temperature; Fishman, 1997;Pollington et al, 2011) -see Figure 2.…”
Section: Lettermentioning
confidence: 99%